Pengaruh Media Sosial Facebook Terhadap Keterlibatan Orang Muda Katolik Dalam Mengikuti Kegiatan Gereja Di Paroki Santo Petrus Erom - Berangka, Dedimus; Via, Machtildis Getrudis (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2024)
The purpose of this research are: 1) to determine whether there is an influence of Facebook use on the involvement of young Catholics of St. Peter Erom in participating in Church activities, 2) to determine the magnitude of the influence of Facebook on the involvement of young Catholics in participating in Church activities, 3) to find out what efforts can be made to increase the involvement of young Catholics in participating in Church activities. This type of research is quantitative with a regression analysis model. The sample of this study was young Catholics of St. Peter Erom parish, totaling 65 people. The instrument used is a questionnaire with Likert scale mode. From the results of the reliability test, an alpha coefficient of 0.945 was obtained, which means the reliability of the instrument is high. From the results of the simple linear regression test with a significance level of 5%, the significance value in the anova table is 0.000, which means that there is an effect of Facebook use on the involvement of young Catholics in Church activities. The R square value is 0.252, which means that the influence of Facebook social media variables on involvement in spiritual activities is 25.2%. Based on the results of this study, it is suggested that increasing cooperation with catechists in planning and implementing programs for young Catholics so that the activities of young Catholics are increasingly programmed and well directed. Provide guidance to Catholic young people, especially to Catholic young people's administrators, so that they can schedule activities properly and sustainable.